(untitled) (Bangladesh Journal of Botany, 2020)
Plants used for making birdlime and indigenous knowledge associated with the practice in Soutpansberg region, Vhembe Biosphere Reserve, Limpopo province, South Africa have been documented. Twelve birdlime-making plant species belonging to Apocynaceae, Celastraceae, Euphorbiaceae, Loranthaceae, Moraceae and Sapotaceae families were recorded. The common species included Maytenus peduncularis (Sond.) Loyes cited by 23.6% informants, Euphorbia pulvinata Marloth (17.2%) and Landolphia kirkii Dyer (12%). Plant parts used were latex (50%), fruit (34%), root (8) and the mixture of latex and fruit (8%). Documentation of plant species used for birdlime-making is of great interest, not only for preservation of the Vhavenḓa’s traditional culture, but also for promoting economic subsistence, nutritional value and livelihood amongst poor and marginalized people.